TimeScale Analysis, Numerical Simulation and Validation of Flame Acceleration, and DDT in Hydrogen–Air Mixtures. Issue 13 (3rd October 2021) - Karanam, Aditya; Ganju, Sunil; Chattopadhyay, Jayanta
ABSTRACT: Flame Acceleration (FA) and Deflagration to Detonation Transition (DDT) are known risks in scenarios involving accidental release and combustion of hydrogen in nuclear reactors. In the present work, chemical timescale and Borghi diagram analysis of hydrogen combustion have been presented. Based on these, a map of the flame propagation in the GraVent shock tube channel has been constructed; and it has been established that the propagation corresponds to the flamelet regime. Subsequently, CFD framework applicable to the flamelet regime such as the geometric approach with turbulent flame closure has been utilized to study deflagrations, FA and DDT. Such methods allow for the computation of pressure transients and flame propagation characteristics with a relatively coarse grid, thereby enabling a balance between computational time and accuracy. Moreover, specific sub-models based on Lewis number and tuned to lean combustion at high pressures have been implemented to further improve the accuracy of the numerical results. All numerical work has been carried out using the open-source numerical platform OpenFOAM. Several numerical simulations with uniform and transversely stratified initial distribution have been carried out and validated with experimental data. In the stratified case, an asymmetric flame front has been observed and is identified to be a key parameter leading to strong FA. Detailed analysis shows that several pressure pulses and shock complexes are formed upstream of the flame. The ensuing shock–flame interaction augments the flame speed ultimately resulting in DDT. Comparative simulations with uniform distribution also show strong FA but DDT does not take place.